2014
DOI: 10.1111/jcpp.12201
|View full text |Cite
|
Sign up to set email alerts
|

Shared familial transmission of autism spectrum and attention‐deficit/hyperactivity disorders

Abstract: Background To determine whether familial transmission is shared between autism spectrum disorders and attention-deficit/hyperactivity disorder, we assessed the prevalence, rates of comorbidity, and familial transmission of both disorders in a large population-based sample of children during a recent seven year period. Methods Study participants included all children born to parents with the Kaiser Permanente Northwest (KPNW) Health Plan between January 1, 1998 and December 31, 2004 (n = 35,073). Children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 39 publications
4
68
1
3
Order By: Relevance
“…Prevalence of (parentreported diagnosis of) ADHD, by contrast, is low (1.4%) in MCS compared to almost 10% among 3-17 year-olds in the US (Bloom, Jones, & Freeman, 2013). In our study, 19.9% of the MCS 7-year-olds with ASD also had ADHD, in line with recent findings about rates in childhood ASD+ADHD co-diagnosis in non-UK population-based samples (Musser et al, 2014). Second, the severity of autism in our sample was unknown.…”
supporting
confidence: 89%
“…Prevalence of (parentreported diagnosis of) ADHD, by contrast, is low (1.4%) in MCS compared to almost 10% among 3-17 year-olds in the US (Bloom, Jones, & Freeman, 2013). In our study, 19.9% of the MCS 7-year-olds with ASD also had ADHD, in line with recent findings about rates in childhood ASD+ADHD co-diagnosis in non-UK population-based samples (Musser et al, 2014). Second, the severity of autism in our sample was unknown.…”
supporting
confidence: 89%
“…A recent review cites evidence for low baseline or resting RSA among children with ADHD (Rash and Aguirre-Camacho 2012). Additionally, children with ADHD exhibit blunted RSA reactivity to both cognitive (Negrao et al 2011) and emotionally challenging tasks (Musser et al 2011, 2014). However, differences in RSA reactivity appear to vary according to type of task utilized, with some studies showing PNS hypo-reactivity and others showing PNS hyper-reactivity in ADHD (Rash and Aguirre-Camacho 2012).…”
mentioning
confidence: 99%
“…These behaviors and disorders are similar to the symptoms of ADHD. Furthermore, it is suggested that ASD shares familial transmission with ADHD, and that ADHD and ASD share a partially overlapping diathesis (Musser et al, 2014). Based on these evidences, we hypothesized that serum levels of OXT in patients with ADHD are lowered than normal controls.…”
mentioning
confidence: 98%